A poética cantada: investigação das habilidades do repentista nordestino - João Miguel Manzolillo Sautchuk (Estudos de Literatura Brasileira Contemporânea, 2010)
The poetical joust, or cantoria, is a poetic and musical art common in Northeast Brazil and is characterized by strophe improvisation, that is, by its making in the very moment of presentation. It is always sung in pairs of poets who, while improvising, dialogue with each other and with the public. They also place themselves in relationship with incorporated esthetic models, with poetic rules, melodic and harmonic patterns, the rhythmic patterns of this poetry, the usual themes and so on, departing from which they must create original texts. While improvising, the singer guides himself by these esthetic models, among which I highlight as the main practical foundation of improvised poetry the poetic rhythm incorporated by these poets.